Urban green and open spaces under pressure: The potential of ecosystem services supply and demand analysis for mediating planning processes in the context of climate change. - Kiese, Nina; Mager, Christoph (My University, 2018)
Die beschriebene Studie präsentiert Ergebnisse des interdisziplinären Forschungsprojekts GREIF (Karlsruher Institut für Technologie und Universität Heidelberg). Ziel des Projektes war es, Bewertungs- und Wahrnehmungskonflikte bei der Abwägung zwischen Klimaschutzstrategien und Klimaanpassungsstrategien im Mehr-Ebenen-System zu identifizieren und gemeinsam mit Praktikern aus der Planung aufzuarbeiten. Vor diesem Hintergrund wurde in dem Projekt die Bewertung und Wahrnehmung von ausgewählten Grün- und Freiflächen in der Metropolregion Rhein-Neckar analysiert.

Climate change is a phenomenon which is discussed to be affecting cities and urbanising societies to a great extent. Thus, land use management of green and open spaces in the direction of climate protection and climate mitigation is an important aspect of sustainable urban and regional planning. However, land use planning holds the potential of causing conflicts between different stakeholders from administration, politics and civil society. The analysis of the demand of ecosystem services may therefore be a useful indicator to identify the interests of different stakeholders. Besides the demand, the analysis of the supply of ecosystem services might help to derive potential offers of climate relevant system functions and to support the planning processes of the areas of interest. Until now, the results of the analysis of ecosystem service supply and demand have been applied predominantly in regional or national contexts. For sustainable urban planning, the local level of observation thus seems to be more relevant. This study presents results of the interdisciplinary research project GREIF (Karlsruhe Institute of Technology and University of Heidelberg, Germany). It aims at identifying ecological and socio-cultural potentials of local urban green and open areas in the Rhine-Neckar metropolitan region, Germany, using an ecosystem service supply and demand approach. Thereby, six ecosystem services of the categories provisioning, regulating and cultural services are analysed for three predefined urban areas. Furthermore, the demand of ecosystem services of local residents as direct users of these areas is determined by conducting comprehensive surveys. The study focuses on the comparison of quantitative supply and qualitative demand data in order to identify discrepancies between supply and demand of ecosystem services. The results will be communicated to administrative bodies and political authorities of the region to enable the integration of additional knowledge into planning decisions. Preliminary results indicate that there are particular differences between the supply and demand of ecosystem services that affect the local residents in a direct way. Where the demand of the ecosystem services food provision and biodiversity is always higher-rated than the supply implies, the ecosystem service demand of climate regulation or renewable energy sources is always lower-rated than the supply indicates. These findings suggest that by incorporating the perceived demands of further stakeholders like planners or politicians, potential conflicting interests between ecosystem service demand and supply might become even more evident. Using this additional knowledge in the early stages of planning processes in the context of climate change might thus help to mitigate conflicts between different stakeholders.
Keywords: Flächennutzungsplanung; Klimaschutz; Nutzungskonflikt; Ökosystemleistung; Metropolregion; Grünfläche; Freifläche; Flächenbewertung